STRATEGI REKRUTMEN PEGAWAI BARU DI MARKAZUL QURAN BUKITTINGGI - Rio Friyadi; Junaidi; Supriadi (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2024)
The purpose of this research is to determine the employee recruitment strategy at Markazul Quran Bukittinggi, an educational institution that is commited to providing quality educational services for students and the community. In this effort, educational institutions need good public relations management to build a positive image, expand cooperation networks, and increase community participation in educational activities. Based on the results of research and discussions, it can be concluded that the implementation of recruitment and selection of teaching staff at Markazul Quran Bukittinggi has been in accordance with the stages that have been determined. The process includes planning, analysis of required positions, and determining requirements. Markazul Quran Bukittinggi prefers to recruit teachers from among their own alumni. Generally, the teachers here come from alumni of the school. Information about teacher vacancies is usually shared through alumni groups or through contact with alumni if there are vacant positions. If no alumni apply, they will recruit from outside by distributing brochures and using social media.